Capital Social e Políticas de Desenvolvimento Territorial: Estudo Multicasos nos Territórios da Cidadania do Rio Grande do Norte - Yuri de Lima Padilha (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
This paper aims to evaluate elements of social capital in Territory of Citizenship Program in Rio Grande do Norte. Unlike other investigations in the theme, it is not intended to measure the stock of social capital, but rather to reveal the phenomenon of social organization and its implications, considering that the territories are constituted by the politics around structures of foment to social capital, which Be they territorial colleges, arenas that include representatives of the various levels of government and civil society. The notion of social capital is in the existence of relations that permeate and sustain the development process in an institutionalized way, normalized or articulated in the form of a social network (COSTA, 2005). The classical studies and definitions of social capital are in Bourdieu (1986), Coleman (1990, 2000) and Putnam (2008). This work has a qualitative character and made use of the case study as the research strategy. Data collection was done through a semi-structured or semipadronized interview. For this purpose, were chosen representatives of the public and social institutions involved in the Açu-Mossoró, Mato Grande and Sertão do Apodi regions. The data analysis and interpretation model was structured from the categorical content analysis of Bardin (2004). In the cases in question, despite the similarity of the general conditions of structure and functioning, the Sertão do Apodi presents qualities superior to others in view of its trajectory of cooperation and social articulation around the technical assistance, historical aspect of the territory.